1997
DOI: 10.1046/j.1365-2842.1997.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Chewing activity and activities of daily living in the elderly

Abstract: The present study was conducted in order to determine the statistical relationship between chewing activity and activities of daily living (ADL) in the elderly. Subjects which took part were 79 elderly individuals (37 males, 42 females) ranging in age from 65 to 74 years. Based on questionnaires regarding diet, a mastication score was determined to evaluate chewing activity in each subject. This score was scaled from 0 to 100%. ADL levels were determined using two indices: the guidelines of the Ministry of Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Four items related to the QOL have been reported to be as follows: behavioural competence, perceived quality of life, objective environment, and psychological well‐being ( Testa & Simonson, 1995). In our previous study, chewing ability was related to not only physical health but also to social health ( Miura, Araki & Umenai, 1997), and thus, in the present study, the PGC morale scale was used to evaluate subjective well‐being and/or life satisfaction. The Japanese version of this scale was developed by Maeda, Asano & Yaguchi (1979).…”
Section: Discussionmentioning
confidence: 99%
“…Four items related to the QOL have been reported to be as follows: behavioural competence, perceived quality of life, objective environment, and psychological well‐being ( Testa & Simonson, 1995). In our previous study, chewing ability was related to not only physical health but also to social health ( Miura, Araki & Umenai, 1997), and thus, in the present study, the PGC morale scale was used to evaluate subjective well‐being and/or life satisfaction. The Japanese version of this scale was developed by Maeda, Asano & Yaguchi (1979).…”
Section: Discussionmentioning
confidence: 99%
“…Probable reasons [3,4] include the impact of tooth loss on digestive function because of food not being chewed adequately; people suffering from tooth loss may also alter their diet or eating efficiency and, thereby, fail to provide the body with adequate nutrition. Studies have also pointed out that chewing ability directly impinges on the quality of life [5,6], life expectancy [7], and the mortality rate [8] among the elderly. Reducing the number of missing teeth in people older than 65 years was the main goal of a World Health Organization initiative in 2000 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Subjective assessments include measurements of the self‐satisfaction of the masticatory function in daily life, as reported by Locker (3). Miura (4) also reported that the life satisfaction of seniors is based mainly on food acceptance. Recently, it was reported that there was a significant correlation between the subjective Food Intake Ability (FIA) and objective bite force (5).…”
Section: Introductionmentioning
confidence: 99%